2017
DOI: 10.3315/jdcr.2016.1234
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma and basal cell carcinoma in the hereditary leiomyomatosis and renal cell cancer syndrome. An expansion of the oncologic spectrum.

Abstract: Background: Hereditary leiomyomatosis and renal cell cancer syndrome (HLRCC) is an autosomal dominant syndrome due to mutation in fumarate hydratase. Patients with HLRCC frequently develop cutaneous and uterine leiomyomata and are at risk for renal cell carcinoma. Rarely, other malignancies have been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, it warrants close follow-up of lesions with biopsies when lesions rapidly increase in size, become ulcerated or are suddenly more painful ( 4 ). In 2016, Sommer et al ( 5 ) reported the case of a melanoma and basal cell carcinoma in a patient with HLRCC and they emphasise the need for close skin surveillance and follow-up ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it warrants close follow-up of lesions with biopsies when lesions rapidly increase in size, become ulcerated or are suddenly more painful ( 4 ). In 2016, Sommer et al ( 5 ) reported the case of a melanoma and basal cell carcinoma in a patient with HLRCC and they emphasise the need for close skin surveillance and follow-up ( 5 ).…”
Section: Discussionmentioning
confidence: 99%